PENGARUH MODEL PROBLEM BASED LEARNING BERBANTUAN MEDIA GAMBAR TERHADAP KETERAMPILAN MENULIS KARANGAN EKSPOSISI SISWA KELAS X SMA EKASAKTI PADANG - Zuraida Khairani; Dwi Mutia Chan; Najmi Nayati (JURNAL KEPEMIMPINAN DAN PENGURUSAN SEKOLAH, 2022)
The purpose of this study there are three things. First, describe the exposition writing skills of class X students of SMA Ekasakti Padang before applying the Problem Based Learning (PBL) model with the help of picture media, Second, describing the exposition writing skills of class X students of SMA Ekasakti Padang after the Problem Based Learning model Learning (PBL) assisted with media images, and Third, analyzing the effect of Problem Based Learning (PBL) assisted by image media on exposition writing essays of class X students of Ekasakti Padang type of research is quantitative research with descriptive analysis research method. Based on the results of data analysis and discussion can be concluded the following. First, the exposition writing skill of class X.2 students of SMA Ekasakti Padang before applying the Problem Based Learning (PBL) model with the help of the picture media was in the "Enough" qualification with an average score of 58. Second, the exposition writing skill of the class students X.2 SMA Ekasakti Padang after applying the Problem Based Learning (PBL) model with the help of picture media is in the "Good" qualification with an average value of 83. Third, there is an influence on the forwarding of Problem Based Learning (PBL) models assisted with image media to exposition writing skills of class X.5 students of Ekasakti Padang, after testing the hypothesis using t-test (t-test). Hypothesis testing results obtained tcount of 7.35 and ttable of 1.70 at P 0.95. Comparison between t count and t table shows that t count is greater than t table. Means, the application of the Problem Based Learning (PBL) model assisted by image media to the exposition writing skills of class X.2 students of SMA Ekasakti Padang, has a significant effect or (H1) is accepted. So, model Problem Based Learning (PBL) Media Assisted Picture worthy applied in learning writing skill exposition.